2016
DOI: 10.1038/srep24806
|View full text |Cite
|
Sign up to set email alerts
|

Rapid climate fluctuations over the past millennium: evidence from a lacustrine record of Basomtso Lake, southeastern Tibetan Plateau

Abstract: Abrupt climate changes and fluctuations over short time scales are superimposed on long-term climate changes. Understanding rapid climate fluctuations at the decadal time scale over the past millennium will enhance our understanding of patterns of climate variability and aid in forecasting climate changes in the future. In this study, climate changes on the southeastern Tibetan Plateau over the past millennium were determined from a 4.82-m-long sediment core from Basomtso Lake. At the centennial time scale, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…AD 1600-2000 [55]. Higher values of TOC, TN, magnetic susceptibility, sand and coarse silt in the sediments of Basomtso Lake, southeastern Tibet, due to higher melt-water run-off owing to warmer conditions during AD 1790-2012, corresponds well with the CWP [66]. The increase in rainfall during the CWP has been linked to an increase in industrial emissions and other anthropogenic factors, as well as the associated increase in surface evaporation and convection in the Indian Ocean [40,70,78].…”
Section: Plos Onementioning
confidence: 66%
See 1 more Smart Citation
“…AD 1600-2000 [55]. Higher values of TOC, TN, magnetic susceptibility, sand and coarse silt in the sediments of Basomtso Lake, southeastern Tibet, due to higher melt-water run-off owing to warmer conditions during AD 1790-2012, corresponds well with the CWP [66]. The increase in rainfall during the CWP has been linked to an increase in industrial emissions and other anthropogenic factors, as well as the associated increase in surface evaporation and convection in the Indian Ocean [40,70,78].…”
Section: Plos Onementioning
confidence: 66%
“…highest ISM rainfall during 1200-800 yr BP. Li et al [66] suggested higher values of TN, TOC, magnetic susceptibility, sand and coarse silt in the sediments of Basomtso Lake, southeastern Tibet, which indicated more sediment input due to an increase in melt-water, due to warmer conditions during AD 1080-1140,.…”
Section: Plos Onementioning
confidence: 99%
“…This result suggests that the organic matter found in the Anguli-nuur Lake sedimentary record is mainly allochthonous in origin (Meyers, 2003). In general, the organic matter content of sediment is related to mean annual precipitation; that is, more precipitation over a lake catchment leads to increases in the transport capacity of streams, and more land-derived organic matter is carried to the lake (Li et al, 2016a; Xiao et al, 2006). Therefore, we interpret the TOC content of core AGL-2010 as a proxy index for precipitation changes in the lake region.…”
Section: Discussionmentioning
confidence: 99%
“…Baksum Lake(30°0′1″N~30°2′53″N,93°53′37″E~94°1′48″E) is located in the southeast of the Qinghai-Tibet Plateau. The elevation of the lake is about 3480 m, the total area of the lake is 26 km 2 , and the maximum depth is about 120 m. The average annual temperature in the lake area is around 6.0 ℃, and the average annual precipitation is 600-700 m. An open freshwater lake with a lake pH of about 7.2 [41]. Yamdroktso (8°27′00″N 29°12′00″N, 90°08′00″E 91°45′00″E) is surrounded by high mountains, the lake is 4441 m above sea level, and the total area is 638 km 2 , the water depth is 20-40 m, and the pH value of the lake is about 9.2-9.3.…”
Section: Study Areasmentioning
confidence: 99%